Role of the AMP kinase in cytokine-induced human EndoC-βH1 cell death. (15th October 2015) - Fred, Rikard G.; Kappe, Camilla; Ameur, Adam; Cen, Jing; Bergsten, Peter; Ravassard, Phillippe; Scharfmann, Raphael; Welsh, Nils
Abstract: The aim of the present investigation was to delineate cytokine-induced signaling and death using the EndoC-βH1 cells as a model for primary human beta-cells. The cytokines IL-1β and IFN-γ induced a rapid and transient activation of NF-κB, STAT-1, ERK, JNK and eIF-2α signaling. The EndoC-βH1 cells died rapidly when exposed to IL-1β + IFN-γ, and this occurred also in the presence of the actinomycin D. Inhibition of NF-κB and STAT-1 did not protect against cell death, nor did the cytokines activate iNOS expression. Instead, cytokines promoted a rapid decrease in EndoC-βH1 cell respiration and ATP levels, and we observed protection by the AMPK activator AICAR against cytokine-induced cell death. It is concluded that EndoC-βH1 cell death can be prevented by AMPK activation, which suggests a role for ATP depletion in cytokine-induced human beta-cell death. Graphical abstract: Highlights: Most IL-1β- and IFN-γ-signaling genes are expressed at similar levels in human EndoC-βH1 cells as in human islets. Cytokine-induced death of EndoC-βH1 cells does not require mRNA transcription, NF-κB/STAT-1 activation and nitric oxide production. Cytokine-induced cell death is paralleled by lowered ATP contents, oxygen consumption and AMPK activation. The AMPK activator AICAR prevented EndoC-βH1 cell death.